2012
DOI: 10.1111/j.1600-6143.2012.04005.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Immunity Rather Than Viral Cytopathology Mediates Polyomavirus-Associated Nephropathy in Mice

Abstract: Nephropathy associated with BK polyomavirus causes kidney allograft dysfunction and failure. Understanding the pathogenesis of polyomavirus‐associated allograft nephropathy (PVAN) is hampered by the species specificity of Polyomaviridae family members. Using a mouse polyomavirus (MPyV) kidney transplant model, we investigated clinically relevant variables that may contribute to PVAN. We found that the timing and source (i.e. donor vs. recipient) of MPyV infection and the titer of the viral inoculum have signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…In a mouse model of kidney transplantation, mouse polyoma virus infection was also shown to enhance anti-donor immunity (23). Moreover, graft nephropathy did not correlate with viral load suggesting that the mechanism for renal injury is not direct viral cytopathology but more likely the interplay between the infection and the alloimmune response (24). In patients, infections have also been associated with episodes of acute rejection.…”
Section: Infections and Alloimmunitymentioning
confidence: 99%
“…In a mouse model of kidney transplantation, mouse polyoma virus infection was also shown to enhance anti-donor immunity (23). Moreover, graft nephropathy did not correlate with viral load suggesting that the mechanism for renal injury is not direct viral cytopathology but more likely the interplay between the infection and the alloimmune response (24). In patients, infections have also been associated with episodes of acute rejection.…”
Section: Infections and Alloimmunitymentioning
confidence: 99%
“…Kidney transplants were performed in 8- to 12-week-old male mice as previously described. 32 There were no significant differences in perioperative mortality between groups, and overall surgical mortality was less than 10%. All transplanted mice were observed for 48 hours after transplant to monitor for immediate complications from surgical technique.…”
Section: Methodsmentioning
confidence: 78%
“…31 Further studies in this model revealed that the adaptive immune response, and not viral cytopathology, was responsible for rejection. 32 These studies established the relationship between alloimmunity and local PyV-mediated allograft injury.…”
mentioning
confidence: 98%
“…Three studies have used the mouse kidney transplant model to investigate the effect of transplant‐associated viral infections . In mice infected with polyomavirus the allograft developed worse histological injury with increased numbers of CD8+ T cells compared with virus‐free recipients .…”
Section: Resultsmentioning
confidence: 99%